Насельники Білостоцького василіанського монастиря (1773–1774 рр.): біографічні відомості - Стецик, Ю. (Краєзнавство, 2019)
На підставі укладених біографічних довідок василіанського чернецтва виокремлено основні просопографічні характеристики: походження (соціальне, територіальне, етноконфесійне), освітня підготовка (світські та чернечі студії), етапи духовної формації (кандидат, новик, брат-профес, ієрей), вікові та фізичні показники (час вступу до чернецтва, тривалість перебування в Чині, роки земного
життя, стан здоров'я), інтелектуальні здобутки (педагогічна та мистецька праця), монастирські
(адміністративні, господарські, освітні) та церковні обов'язки. On the basis of the completed biographical references of the Basilian monasticism the main prosopographic
characteristics are distinguished: origin (social, territorial, ethno-confessional), educational training (secular and
monastic studios), stages of spiritual formation (candidate, novice, brother-professor, priest), age and physical characteristics
(time of entry to monasticism, length of stay in the Order, years of earthly life, health status), intellectual
achievements (pedagogical and artistic work), monastic (administrative, economic, educational) and church duties.
In the short-term period under consideration, the ascension inhabited by the territory of the former Commonwealth
(Volyn, Podil, Kyiv and ancient Rus’ voivodships) was inhabited by the ascension monastery and represented
various social strata (gentry, peasantry, burgesses). They formed a monastic community that consisted of age groups:
older (over 50 years), young (30–40 years), and youth (17–15 years) generations. The older generation, who have
gained considerable ascetic experience (over 15 years of spiritual ministry), were actively involved in the spiritual
and intellectual formation of young monasticism, which underwent rhetoric studies. All of them were united by a
united faith and a desire to abide by the rules of St. Basil the Great and the Constitutions of the Basilian Order.